Answer:
1 3/4 meters
Step-by-step explanation:
1.75 = 1 3/4 [think of it as since 3 quarters equals 75 cents, and 4 quarters equals 100 cents or a dollar.]
So, 1 3/4 meters
What is the value of the product (3-21) (3 + 21)?
The value of the product (3 - 21) * (3 + 21) is -432, obtained by applying the distributive property.
To find the value of the product (3 - 21) * (3 + 21), we can use the distributive property or the difference of squares identity. Here's how it works:
(3 - 21) * (3 + 21) = (3 - 21) * [(3) + (21)] (Apply the distributive property)
Now, let's calculate each part:
1. (3 - 21) = -18
2. (3 + 21) = 24
Now, we multiply these results together:
-18 * 24 = -432
So, the value of the product (3 - 21) * (3 + 21) is -432.
For such more questions on product
https://brainly.com/question/1712056
#SPJ2
Final answer:
The product of (3-21) and (3 + 21) is -324.
Explanation:
The value of the product (3-21) (3 + 21) is -324.
To find the product, first calculate the values within the parentheses:
3 - 21 = -18
3 + 21 = 24
Multiply these two values: -18 * 24 = -324.
Question 4 of 10
2 Points
Rewrite the following linear equation in slope-intercept form. Write your
answer with no spaces.
v+4= -2(x-1)
Answer here
SUBMIT
Are you sure that one of the variables is v and not y?
v+4= -2(x-1)
Since you posted v, I will use v in place of y.
v + 4 = -2x + 2
v = -2x + 2 - 4
v = -2x - 2
Done!
3. Juliet rides her bike. During her ride, elevation
increases a total of 4,228 feet, an increase of 75
feet per mile. How many miles does Juliet ride?
Answer:
56.4 miles
Step-by-step explanation:
4228/75 = 56.37333333
simplify the trigonometric expression tan(2x)/tan(x) using double-angle identities !!
A. 2/1-tan^2(x)
B. 2tan(x)/1-tan^2(x)
C. 2tan(x)/1-tan^3(x)
D. tan(x)
The correct solution is,
⇒ 2 / (1 - tan²x)
What is an expression?Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The expression is,
⇒ tan (2x) / tan x
Now, We know that;
tan 2x = (2 tanx / 1 - tan²x)
Hence, We can simplify as;
⇒ tan (2x) / tan x
⇒ (2tan (x) /1 - tan²x) / tan x
⇒ 2 / (1 - tan²x)
Thus, The correct solution is,
⇒ 2 / (1 - tan²x)
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ2
The expression tan(2x)/tan(x) simplifies using the double-angle identity for tangent to 2/(1 - tan^2(x)), which corresponds to Option A.
To simplify the trigonometric expression tan(2x)/tan(x) using double-angle identities, we can use the double-angle identity for tangent:
tan(2x) = 2tan(x)/(1 - tan2(x)).
Now, if we divide tan(2x) by tan(x), we get:
tan(2x)/tan(x) = (2tan(x)/(1 - tan2(x)/tan(x).
With tan(x) in the numerator and denominator, it cancels out, leaving:
2/(1 - tan2(x)).
Therefore, the correct answer is Option A: 2/(1 - tan2(x)).
If a polynomial function f(x) has roots 6 and square root of 5, what must also be a root of f(x)?
A. -6
B. Square root of -5
C. 6 - Square root of 5
D. 6 + Square root of 5
Answer:
-[tex]\sqrt{5}[/tex]
Step-by-step explanation:
A root with square root or under root is only obtained when we take the square root of both sides. Remember that when we take a square root, there are two possible answers:
One answer with positive square rootOne answer with negative square rootFor example, for the equation:
[tex]x^{2}=3[/tex]
If we take the square root of both sides, the answers will be:
[tex]x=\sqrt{3} \text{ or } x= -\sqrt{3}[/tex]
Only getting one solution with square root is not possible. Solutions with square root always occur in pairs.
For given case, the roots are 6 and [tex]\sqrt{5}[/tex]. Therefore, the 3rd root of the polynomial function f(x) had to be -[tex]\sqrt{5}[/tex]
It seems you made error while writing option B, it should be - square root of 5.
Answer:
B
Step-by-step explanation:
30 POINTS WILL MARK BRAINLIEST!!
Multiply each equation by a number that produces opposite coefficients for x or y.
The coefficient of x needs to be 2.
The current coefficient is 2/5.
To eliminate the 5 in the denominator, we can multiply the equation by 5.
We get
[tex]2x + 30y = - 50[/tex]
Now, to solve the equations, all we need to do is add them.
Hope this helps!
What are the possible steps involved in solving the equation shown? Select three options.
3.5 + 1.2(6.3 – 7x) = 9.38
Add 3.5 and 1.2.
Distribute 1.2 to 6.3 and –7x .
Combine 6.3 and –7x .
Combine 3.5 and 7.56.
Subtract 11.06 from both sides.
Answer:
Option B, C and D are correct choices.
Step-by-step explanation:
We have been given an equation [tex]3.5+1.2(6.3-7x)=9.38[/tex]. We are asked to choose the steps that are involved in solving the equation.
Let us solve the equation.
Using distributive property [tex]a(b+c)=ab+ac[/tex], we will distribute 1.2 to 6.3 and [tex]-7x[/tex].
[tex]3.5+1.2*6.3-1.2*7x=9.38[/tex]
[tex]3.5+7.56-8.4x=9.38[/tex]
Therefore, option B is the correct choice.
Now, we will combine like terms.
[tex]11.06-8.4x=9.38[/tex]
Therefore, option C is the correct choice.
Now, we will subtract 11.06 from both sides of our equation.
[tex]11.06-11.06-8.4x=9.38-11.06[/tex]
[tex]-8.4x=-1.68[/tex]
Therefore, option D is the correct choice.
Now, to solve for x, we need to divide both sides of our equation by [tex]-8.4[/tex]
[tex]\frac{-8.4x}{-8.4}=\frac{-1.68}{-8.4}[/tex]
[tex]x=0.2[/tex]
Answer:
Distribute 1.2 to 6.3 and –7x;
Combine 3.5 and 7.56.
Subtract 11.06 from both sides.
Step-by-step explanation:
To answer this expression. Let's follow P.E.M.D.A. order, the acronym for PArenthesis, Exponents, Multiplication, Division and Addends. So distributing the factor 1.2 to the parenthesis content:
[tex]3.5+1.2(6.3-7x)=9.38 \\3.5+7.56-8.4x=9.38[/tex]
Then adding the 3.5 to 7.56 to simplify it:
[tex]3.5+7.56-8.4x=9.38\\\11.06-8.4x=9.38[/tex]
The next step in order to isolate is to subtract 11.06 from both sides
[tex]11.06-8.4x-11.06=9.38-11.06[/tex]
Then it goes on
[tex]-8.4x=-1.68\:\:*(-1)\\8.4x=1.68\Rightarrow x=\frac{1.68}{8.4}\Rightarrow x=\frac{1}{5}\\S=\{ {\frac{1}{5}\}[/tex]
in a class of 30 students there are 17 girls. two students are picked randomly to represent the class in the SRC. determine the probability that:
a. both students are boys
b. both students are girls
c. one of the students is a boy
Answer:
See below in bold,.
Step-by-step explanation:
There are 30-17 = 13 boys in the class.
a. Prob(First is a boy ) = 13/30 and Prob( second is a boy = 12/29).
As these 2 events are independent:
Prob( 2 boys being picked) = 13/30 * 12/29 = 26/145 or 0.179 to the nearest thousandth.
b. By a similar method to a:
Prob ( 2 girls being picked) = 17/30 * 16/29 = 136/435 = 0.313 to the nearest thousandth.
c. Prob (First student is a boy and second is a girl) = 13/30 * 17/29 = 221/870.
Prob ( first student is a girl and second is a boy) = 17/30 * 13/29 = 221/870
These 2 events are not independent so they are added:
Prob( one of the students is a boy) = 2 (221/870 = 221/435 = 0.508 to the nearest thousandth.
Terrance invested money in a technology stock whose growth is modeled by the function f(x) = 0.01(2)x, where x represents number of days. Find the approximate average rate of change from day 3 to day 8.
A 0.496
B 2.016
C 2.48
D 5
Answer:
Option A 0.496
Step-by-step explanation:
we know that
The approximate average rate of change is equal to
[tex]\frac{f(8)-f(3)}{8-3}[/tex]
[tex]\frac{f(8)-f(3)}{5}[/tex]
we have
[tex]f(x)=0.01(2^{x})[/tex]
Find f(8)
For x=8
[tex]f(8)=0.01(2^{8})=2.56[/tex]
Find f(3)
For x=3
[tex]f(8)=0.01(2^{3})=0.08[/tex]
Find the approximate average rate of change
[tex]\frac{f(8)-f(3)}{5}[/tex]
substitute
[tex]\frac{2.56-0.08}{5}=0.496[/tex]
Answer: A, 0.496
Step-by-step explanation:
To find the difference, you need to raise the base, 2, to each number since x represents the days.
Raise 2 to the power of 3:
2^3 = 8
multiply by 0.01
0.01 * 8 = 0.08
That is the growth of day three.
Now do the same with the 8
Raise 2 to the power of 8
2^8 = 256
Now multiply that by 0.01
0.01 * 256 = 2.56
Now use this formula: f(b) - f(a)/b - a
2.56 - 0.08/8 - 3
Subtract 0.08 from 2.56
2.56 - 0.08 = 2.48
Subtract 3 from 8
8 - 3 = 5
Now divide: 2.48/5 = 0.496
0.496 is the average rate of change between day 3 and day 8. Also I got 100 on the test so I know the answer :))
Which statement proves that △XYZ is an isosceles right triangle? XZ ⊥ XY XZ = XY = 5 The slope of XZ is , the slope of XY is , and XZ = XY = 5. The slope of XZ is , the slope of XY is , and the slope of ZY = 7.
Answer:
The slope of XZ is 3/4 , the slope of XY is -4/3 , and XZ = XY = 5 ⇒ 3rd answer
Step-by-step explanation:
* Lets look to the attached figure to solve the problem
- To prove that the Δ XYZ is an isosceles right triangle, you must
find two sides the product of their slopes is -1 and they are equal
in lengths
- From the figure the vertices of the triangle are;
X = (1 , 3) , Y = (4 , -1) , Z = (5 , 6)
- The slope of the line whose endpoints are (x1 , y1) and (x2 , y2)
is [tex]m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
∵ The slope of [tex]XY=\frac{-1-3}{4-1}=\frac{-4}{3}[/tex]
∵ The slope of [tex]XZ=\frac{6-3}{5-1}=\frac{3}{4}[/tex]
∴ The slope of XY = -4/3 , the slope of XZ = 3/4
∵ -4/3 × 3/4 = -1
∴ XY ⊥ XZ
∴ ∠ X is a right angle
∴ Δ XYZ is a right triangle
- The distance between the two points (x1 , y1) and (x2 , y2) is
[tex]d=\sqrt{(x_{2}-x_{1})^{2}+(y_{2}-y_{1})^{2}}[/tex]
∵ [tex]XY=\sqrt{(4-1)^{2}+(-1-3)^{2}}=\sqrt{9+16}=\sqrt{25}=5[/tex]
∵ [tex]XZ=\sqrt{(5-1)^{2}+(6-3)^{2}}=\sqrt{16+9}=\sqrt{25}=5[/tex]
∴ XY = XZ = 5
∴ Δ XYZ is an isosceles right triangle
* The statement which prove that is:
The slope of XZ is 3/4 , the slope of XY is -4/3 , and XZ = XY = 5
Answer:
its C
Step-by-step explanation:
yw :)
solve for the indicated variable
ax+r=7, for x
Answer:
x = [tex]\frac{7 - r}{a}[/tex]
Step-by-step explanation:
ax+r=7
ax = 7 - r
x = [tex]\frac{7 - r}{a}[/tex]
Solve the compound inequality 6b < 36 or 2b + 12 > 6.
Answer:
Answer is all real numbers.
<~~~~~~~~~~~~~~~~~~~~~~~~~~~~~>
---------(-3)---------------------(6)-------------
Step-by-step explanation:
6b<36
Divide both sides by 6:
b<6
or
2b+12>6
Subtract 12 on both sides:
2b>-6
Divide both sides by 2:
b>-3
So we want to graph b<6 or b>-3:
o~~~~~~~~~~~~~~~~~~~~~~~~~~ b>-3
~~~~~~~~~~~~~~~~~~~~~~~~o b<6
_______(-3)____________(6)___________
So again "or" is a key word! Or means wherever you see shading for either inequality then that is a solution to the compound inequality. You see shading everywhere so the answer is all real numbers.
<~~~~~~~~~~~~~~~~~~~~~~~~~~~~~>
---------(-3)---------------------(6)-------------
Answer:
All real numbers [tex](-\infty, \infty)[/tex]
Step-by-step explanation:
First we solve the following inequality
[tex]6b < 36[/tex]
Divide by 6 both sides of the inequality
[tex]b<\frac{36}{6}\\\\b<6[/tex]
The set of solutions is:
[tex](-\infty, 6)[/tex]
Now we solve the following inequality
[tex]2b + 12 > 6[/tex]
Subtract 12 on both sides of the inequality
[tex]2b + 12-12 > 6-12[/tex]
[tex]2b> -6[/tex]
Divide by 2 on both sides of the inequality
[tex]\frac{2}{2}b> -\frac{6}{2}[/tex]
[tex]b> -3[/tex]
The set of solutions is:
[tex](-3, \infty)[/tex]
Finally, the set of solutions for composite inequality is:
[tex](-\infty, 6)[/tex] ∪ [tex](-3, \infty)[/tex]
This is: All real numbers [tex](-\infty, \infty)[/tex]
Mia removes the plug from a trough to drain the water. The volume, in gallons, in the trough after it has been unplugged can be modeled by the expression 10x2 −19x + 6, where x is time in minutes. Choose the appropriate form of the expression that would reveal the time in minutes when the trough is empty. 10(0)2 − 19(0) + 6 10(x − 6)2 − 1 10(x − 1)2 − 6 (5x − 2)(2x − 3)
Answer:
The correct option is D) (5x − 2)(2x − 3).
Step-by-step explanation:
Consider the provided expression.
[tex]10x^2-19x+6[/tex]
Where x is time in minutes.
We need to find the appropriate form of the expression that would reveal the time in minutes when the trough is empty.
When the trough is empty the whole expression becomes equal to 0.
Substitute the whole expression equal to 0 and solve for x that will gives us the required expression.
[tex]10x^2-19x+6=0[/tex]
[tex]10x^2-15x-4x+6=0[/tex]
[tex]5x(2x-3)-2(2x-3)=0[/tex]
[tex](5x-2)(2x-3)=0[/tex]
Now consider the provided option.
By comparison the required expression is D) (5x − 2)(2x − 3).
Hence, the correct option is D) (5x − 2)(2x − 3).
Answer:
The correct answer is D
Step-by-step explanation:
If the x- and y-values in each pair of a set of ordered pairs are interchanged, the resulting set of ordered pairs is known as the _______.
Answer:
Inverse of a function
Step-by-step explanation:
If the x- and y-values in each pair of a set of ordered pairs are interchanged, the resulting set of ordered pairs is known as the inverse of a function.
For example, given the following function:
y = 2x
If x=0 → y= 0
If x=1 → y= 2
If x=2 → y= 4
Now, if we find the inverse of the function:
y = 2x → x = 2y → y = x/2
Now:
If x=0 → y= 0
If x=2 → y= 1
If x=4 → y= 2
Comparing both cases, you will notice that the ordered pairs are effectively interchanged.
The resulting set of ordered pairs formed by interchanging the x- and y-values in each pair is known as the inverse of the original set.
Explanation:If the x- and y-values in each pair of a set of ordered pairs are interchanged, the resulting set of ordered pairs is known as the inverse of the original set. In mathematics, an ordered pair is a pair of objects written in a specific order, typically as (x,y). If you switch the positions of the elements to form (y,x), you create an ordered pair that represents the inverse relationship. This is particularly relevant in the context of functions and relations on a Cartesian coordinate system. The concept of ordered pairs is fundamental to understanding mappings and the domain and range of relations.
For example, if you have an ordered pair representing a function, such as (3,4), its inverse would be (4,3). This reflects a new relationship where the original output is now the input and vice versa. The set of all such inverted pairs from a function forms the inverse function, provided that each y value is associated with only one x value (the function is one-to-one).
A relation where the ordering of elements matters contrasts with a set where the order does not affect the identity of the set. Hence, achieving an inverse relationship by switching the ordered pairs is a useful tool in mathematical problem-solving and analysis.
Point A represents a complex number plotted on a complex plane. Click the point that represents its complex conjugate. PICTURE DOWN BELOW. Which red point would it be?
Answer:
The red point (-4 , -6)
Step-by-step explanation:
* Lets revise the complex number
- The complex number z = a + bi, where a is the real part and b is the
imaginary part
- The real part represented by the x-axis and the imaginary part
represented by the y-axis
- The value of i is √(-1)
- The complex conjugate of a complex number is the number with an
equal real part and an imaginary part equal in magnitude but opposite
in sign
- Ex: the conjugate of a + bi is a - bi
* Lets solve the problem
∵ A is an complex number
∵ The x-coordinate of A is -4 and the y-coordinate of it is 6
∵ The x-axis is the real axis and y-axis is the imaginary axis
∴ A = -4 + 6i
∵ The conjugate numbers are equal in real part and the imaginary
part equal in magnitude and different in sign
∴ The conjugate of A = -4 - 6i
- From the graph The red point (-4 , -6) represents the complex
conjugate of point A
Julio cut one dozen roses from his garden. He gave five to his mother and two to his sister. He cut nine more roses and gave four to his grandmother. How many cut roses did he have left?
Will reward brainlist
Answer:
he would have 10 roses left
Step-by-step explanation:
12-5=7-2=5
5+9=14-4=10
1 mile equals approximately 1.6 kilometers. Approximately how many kilometers are in 4 miles? A) 4 kilometers B) 6 kilometers C) 8 kilometers D) 10 kilometers
Answer:
6
Step-by-step explanation:
I took the same test
the vertex of this parabola is at (-5,-2). when the x-value is -4, the y-value is 2. what is the coefficient of the squared term in the parabolas equation
Answer:
First case The coefficient of the squared term is 4
Second case The coefficient of the squared term is 1/16
Step-by-step explanation:
I will analyze two cases
First case (vertical parabola open upward)
we know that
The equation of a vertical parabola in vertex form is equal to
[tex]y=a(x-h)^{2}+k[/tex]
where
a is the coefficient of the squared term
(h,k) is the vertex
we have
(h,k)=(-5,-2)
substitute
[tex]y=a(x+5)^{2}-2[/tex]
Find the value of a
Remember that
when the x-value is -4, the y-value is 2.
substitute
For x=-4, y=2
[tex]2=a(-4+5)^{2}-2[/tex]
[tex]2=a(1)-2[/tex]
[tex]a=2+2=4[/tex]
the equation is equal to
[tex]y=4(x+5)^{2}-2[/tex]
therefore
The coefficient of the squared term is 4
Second case (horizontal parabola open to the right)
we know that
The equation of a horizontal parabola in vertex form is equal to
[tex]x=a(y-k)^{2}+h[/tex]
where
a is the coefficient of the squared term
(h,k) is the vertex
we have
(h,k)=(-5,-2)
substitute
[tex]x=a(y+2)^{2}-5[/tex]
Find the value of a
Remember that
when the x-value is -4, the y-value is 2.
substitute
For x=-4, y=2
[tex]-4=a(2+2)^{2}-5[/tex]
[tex]-4=a(4)^{2}-5[/tex]
[tex]-4+5=a(16)[/tex]
[tex]a=1/16[/tex]
the equation is equal to
[tex]x=(1/16)(y+2)^{2}-5[/tex]
therefore
The coefficient of the squared term is 1/16
to better understand the problem see the attached figure
What is the value of X?
Answer:
x ≈ 6.6 cmStep-by-step explanation:
It's a right triangle.
Use the Pythagorean theorem:
[tex]leg^2+leg^2=hypoyenuse^2[/tex]
We have:
[tex]leg=13.5\ cm,\ leg=x\ cm,\ hypotenuse=(x+8.45)\ cm[/tex]
Substitute:
[tex]13.5^2+x^2=(x+8.45)^2\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\\\182.25+x^2=x^2+2(x)(8.45)+8.45^2\qquad\text{subtract}\ x^2\ \text{from both sides}\\\\182.25=16.9x+71.4025\qquad\text{subtract 71.4025 from both sides}\\\\110.8475=16.9x\qquad\text{divide both sides by 16.9}\\\\\dfrac{110.8475}{16.9}=x\to x\approx6.6\ cm[/tex]
Un muchacho compra el mismo numero de lapices que de lapiceros por 90 soles.Cada laliz le cuesta 3 soles y cada lapicero 7 soles. ¿Cuantos lapices y lapiceros ha comprado?
The boy bought 9 pencils and 9 pens, with a total cost of 90 soles. This calculation is based on the cost of 3 soles per pencil and 7 soles per pen, resulting in a total expenditure that aligns with the given information.
1: Define the costs.
We know the cost of each pencil and pen:
Pencils: 3 soles each
Pens: 7 soles each
2: Let x be the number of items.
Since the boy buys the same number of pencils and pens, let x represent the number of each item he buys.
3: Set up the total cost equation.
The total cost he spends is 90 soles. We can express this as an equation:
Total cost = Pencils cost + Pens cost
90 soles = (x pencils * 3 soles/pencil) + (x pens * 7 soles/pen)
4: Simplify and solve for x.
Combine like terms:
90 soles = 3x soles + 7x soles
90 soles = 10x soles
x = 90 soles / 10 soles/item
x = 9 items
5: Find the number of pencils and pens.
Since x represents both the number of pencils and pens, he bought 9 pencils and 9 pens.
Therefore, the boy bought 9 pencils and 9 pens.
Complete question:
A boy buys the same number of pencils as pencils for 90 soles. Each pencil costs 3 soles and each pencil 7 soles. How many pencils and pens has he bought?
What is a plane figure bounded by four straight line
Answer:
A plane figure with 4 sides is called a quadrilateral.
A quadrilateral is a plane figure bounded by four straight lines in mathematics.
Plane figure bounded by four straight lines: In mathematics, a quadrilateral is a plane figure bounded by four straight lines. Examples of quadrilaterals include squares, rectangles, parallelograms, and trapezoids.
Indicate which two quadrants “theta” could terminate if sin theta = 4/5
Answer:
1st and 2nd quadrants
Step-by-step explanation:
You have sine is positive since it is 4/5.
Sine is the y-coordinate.
On the coordinate plane y is positive in the 1st and 2nd quadrants.
The values of θ that could terminate when sin θ = 4/5 are in the first and second quadrants. In the first quadrant, both the sine and cosine values are positive, while in the second quadrant, only the sine value is positive.
Explanation:To find the quadrants where θ could terminate when sin θ = 4/5, we need to examine the values of sin θ in each quadrant. The sine function is positive in the first and second quadrants so that θ could terminate in either of these quadrants. In the first quadrant, the sine and cosine values are positive, while in the second quadrant, only the sine value is positive.
Learn more about quadrants here:https://brainly.com/question/26426112
#SPJ3
Cube A has an edge length....
Answer:
C. 3 times
Step-by-step explanation:
If cube a has an edge length of 2 and cube b has an edge length of 6,the volume of cube b than cube a is 3 times greater.
For this case we have that by definition, the volume of a cube is given by:
[tex]V = l ^ 3[/tex]
Where:
l: It's the side of the cube
Cube A:
[tex]l = 2\\V = 2 ^ 3 = 8 \ units ^ 3[/tex]
Cube B:
[tex]l = 6\\V = 6 ^ 3 = 216 \ units ^ 3[/tex]
We divide:
[tex]\frac {216} {8} = 27[/tex]
Thus, the volume of cube B is 27 times larger than that of cube A.
Answer:
Option A
What’s equivalent to 1/7-3(3/7n-2/7) combine like terms
Answer:
(1/7)(-9n + 7)
Step-by-step explanation:
1/7-3(3/7n-2/7) can be factored: factor out 1/7.
We get: (1/7)[1 - 3(3n - 2)], or
(1/7)[1 - 9n + 6], or
(1/7)(-9n + 7)
Is the equation below a sum of cubes
125x3 +169
Answer:
NOStep-by-step explanation:
[tex]\text{Because}\\\\125x^3=5^3x^3=(5x)^3\qquad\bold{it's\ a\ cube}\\\\169=13^2\qquad\bold{it's \ a \ square}\\\\125x^3+169=(5x)^3+13^2[/tex]
[tex]13-\text{it's a prime number}[/tex]
How do the solutions to an equation relate to the graph of the equation?
How do you solve a system of equations approximately using graphs and tables?
need it in 2 paragraph I will 100% leave thanks and 5 star
Answer:
Ok
Step-by-step explanation: what is this???????
Solve by using the quadratic formula.
3psquared+7p+2=0
Answer:
[tex]\large\boxed{x=-2\ or\ x=-\dfrac{1}{3}}[/tex]
Step-by-step explanation:
The quadratic formula of a quadratic equation
[tex]ax^2+bx+c=0\\\\x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
We have the equation:
[tex]3p^2+7p+2=0\to a=3,\ b=7,\ c=2[/tex]
Substitute:
[tex]b^2-4ac=7^2-4(3)(2)=49-24=25\\\\\sqrt{b^2-4ac}=\sqrt{25}=5\\\\x_1=\dfrac{-7-5}{2(3)}=\dfrac{-12}{6}=-2\\\\x_2=\dfrac{-7+5}{2(3)}=\dfrac{-2}{6}=-\dfrac{1}{3}[/tex]
Answer:
-1/3,-2
Step-by-step explanation:
The quadratic formula is [-b±√(b^2-4ac)]/2a. In this equations 3p^2 is a, 7p is b, and 2 is c.
Then just plug in the numbers.
[-7±√((-7^2)-4(3)(2)]/2(3)
[-7±√(25)]/6
(-7+5)/6 and (-7-5)/6
-1/3 and -2 are the answers, if you plug these numbers into the original equation, you find that they equal 0 which means that they work.
What is x, if the volume of the cylinder is 768pi rcm3?
let's recall Cavalieri's Principle, solids with equal altitudes and cross-sectional areas at each height have the same volume, so even though this cylinder is slanted with a height = x and a radius = 8, the cross-sectional areas from the bottom to top are the same thickness and thus the same area, so its volume will be the same as a cylinder with the same height and radius that is not slanted.
[tex]\bf \textit{volume of a cylinder}\\\\ V=\pi r^2 h~~ \begin{cases} r=radius\\ h=height\\ \cline{1-1} r=8\\ h=x\\ V=768\pi \end{cases}\implies 768\pi =\pi (8)^2(x)\implies 768\pi =64\pi x \\\\\\ \cfrac{768\pi }{64\pi }=x\implies 12=x[/tex]
What is the distance from (3 1/2, 5) to (3 1/2, –12)?
Answer:
0, 17
3 1/2, 5
-3 1/2, -12
0, 17
Answer:
17
Step-by-step explanation:
First label the 2 points.
A = (3, 1/2, 5), B = (3, 1/2, -12)
Then calculate the vector from A to B:
[tex]\vect{AB} = (0, 0, -17)[/tex]
And then calculate it's length by the formula:
[tex]||\vect{a}|| = \sqrt{x^2 + y^2 + z^2}[/tex], where x, y, z are the coordinates related to the vector.
[tex]||\vect{AB}|| = \sqrt{0^2 + 0^2 + (-17)^2} = \sqrt{(-17)^2} = |17| = 17[/tex]
The blue segment below is a diameter of O. What is the the length of the radius of the circle?
Answer:
2.95
Step-by-step explanation:
The radius of a circle is half of the diameter.
r = (1/2)d
r = (1/2)(5.9)
r = 2.95
Answer:
radius = 2.95
Step-by-step explanation:
The radius is the distance from the centre O to the circumference and is one half the diameter,
radius = 0.5 × 5.9 = 2.95